Cellular uptake and toxicity of gold nanoparticles on two distinct hepatic cell models. (February 2021) - Enea, Maria; Pereira, Eulália; Costa, Joana; Soares, Maria Elisa; Dias da Silva, Diana; Bastos, Maria de Lourdes; Carmo, Helena Ferreira
Abstract: Gold nanoparticles (AuNPs) have huge potential for various biomedical applications, but their successful use depends on their uptake and possible toxicity in the liver, their main site for accumulation. Therefore, in this work we compared the cytotoxic effects induced by AuNPs with different size (~ 15 nm and 60 nm), shape (nanospheres and nanostars) and capping [citrate- or 11-mercaptoundecanoic acid (MUA)], in human HepaRG cells or primary rat hepatocytes (PRH) cultivated with serum-free or Foetal Bovine Serum (FBS)-supplemented media. The safety assessment of the AuNPs demonstrated that overall they present low toxicity towards hepatic cells. Among all the tested AuNPs, the smaller 15 nm spheres displayed the highest toxicity. The toxicological effect was capping, size and cell-type dependent with citrate-capping more toxic than MUA (PRH with FBS), the 15 nm AuNPs more toxic than 60 nm counterparts and PRH more sensitive, as compared to the HepaRG cells. The incubation with FBS-free media produced aggregation of AuNPs while its presence greatly influenced the toxicity outcomes. The cellular uptake of AuNPs was shape, size and capping dependent in PRH cultivated in FBS-supplemented media, and significantly different between the two types of cells with extensively higher internalization of AuNPs in PRH, as compared to the HepaRG cells. These data show that the physical-chemical properties of AuNPs, including size and shape, as well as the type of cellular model, greatly influence the interaction of the AuNPs with the biological environment and consequently, their toxicological effects. Graphical abstract: Unlabelled Image Highlights: Primary rat hepatocytes are more sensitive to the effect of gold nanoparticles compared to human hepatoma HepaRG cells. Gold nanoparticles presented low cytotoxicity and high internalization on in vitro hepatic cell model. The presence of Foetal Bovine Serum highly influence the stability, cytotoxicity and cellular uptake of gold nanoparticles.